Trends of Urbanisation in India: A Test of Some Alternative Hypothesis - Planning Commission (Planning Commission, 1982)
This paper is an attempt to analyse the trend of urbanisation during the period 1901-71 and identify the factors responsible for it. Structural changes in the six town class sizes during the period of study have been analysed. Different forms of trend equation have been fitted to the sizes of urban population to understand if growth of cities exhibit asymptotic trend. Law of proportionate effect and theory of rank size distribution have been used to understand the direction of urbanisation. Lastly, population in cities has been regressed with dif explanatory variables to isolate factors which are most significantly associated with urbanisation,
Planning Commission Government of India (UNDP Transport Policy Planning Project)